The Reproductive Toxicity of the Ethanolic Extract of Tetrapleura tetraptera Pods on Male and Female Swiss Albino Mice (Mus musculus) - Adeola Michael Oloyede * (Lorestan University of Medical Sciences, 2018)
Background and Aim: Tetrapleura tetraptera is used to treat various maladies in southwestern Nigeria, particularly among the Yoruba tribe. This research was designed to examine the reproductive toxicity of the ethanolic extract of T. tetraptera in male and female mice respectively. Materials and Methods: To conduct a spermatogenic study, 20 male mice weighing  averagely 19 - 25g were divided into four groups of 5 mice. Groups 1 - 3 were administered T. tetraptera extract of 200, 100, and 50m/kg-1 bwt. orally respectively. The control group was administered distilled water. All the groups were treated for 40 days after which they were sacrificed via jugular puncture. The testes were excised and sperms collected from epididymis for the preparation of slides. Various histologic studies have been carried out on the testes. For teratogenic studies, 20 female mice weighing averagely between 15- 20g were divided into four groups based on body weight, and then a male mouse was placed in each cage to ensure mating. Animals in group 1 - 3 received  200, 100, and 50m/kg-1  bwt of  the extract orally, while the control group received distilled water. The animals were treated for 40 days after which their uteri were excised to observe embryos or foetuses. Results: In the spermatogenic studies, some abberrant sperm cells such as sperms without hook, armophous head, two tails, pin head and clusterd tails were observed. Histology revealed slight modification of  histoachitechure of the testes like necrotic shreded cells with degenerating basal membrane, non-differentiated germinal cells, artrophy of sertoli cells and vacuolated sertoli cells. No embryo or foetus was found in the female reproductive organs after excission in all the mice treated with extract, but each mouse in  the control group conceived and delivered an average of 6 mice. Conclusion: T.tetraptera may contain some cytotoxic agents  inhibiting implantation and distorting sperm morphology. The extract may be unsafe for consumption at the doses investigated.